(untitled) (Conferencea, 2022)
Within three months, the Cabinet of Ministers of the Republic of Uzbekistan approved the Concept of accelerated development of the textile and clothing industry for 2019-2025. support-based production and export, research of domestic and foreign markets for the sale of textile products, implementation of measures to ensure the competitiveness of products in domestic and foreign markets, the creation of a single chain of value added, to increase the volume of textile exports to 7 billion US dollars by 2025 through the processing of the entire volume of cotton yarn [1].